2017
DOI: 10.1002/chem.201605846
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of Excess Electron Transfer through LUMO Gradients in DNA Containing Phenanthrenyl Base Surrogates

Abstract: The modulation of excess electron transfer (EET) within DNA containing a dimethylaminopyrene (C-AP) as an electron donor and 5-bromouracil ( Br dU) as a electron acceptor through phenanthrenyl pairs (phen-R) could be achieved by modifying the phenanthrenyl base surrogates with electron withdrawing and donating groups. Arranging the phenanthrenyl units to form a descending LUMO gradient increased the EET efficiency compared to the electron transfer through uniform LUMOs or an ascending LUMO gradient.The well-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[20][21][22] DNA and its analogues can be used as templates to construct helical chromophore associates through π-interactions in a precise manner. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Helical chromophore associates have unique properties that differ significantly from those of the monomeric state. The manner in which chromophores associate depends on the structure of the DNA-template.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] DNA and its analogues can be used as templates to construct helical chromophore associates through π-interactions in a precise manner. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Helical chromophore associates have unique properties that differ significantly from those of the monomeric state. The manner in which chromophores associate depends on the structure of the DNA-template.…”
Section: Introductionmentioning
confidence: 99%
“…DNA and its analogues can be used as templates to construct helical chromophore associates through π‐interactions in a precise manner [23–38] . Helical chromophore associates have unique properties that differ significantly from those of the monomeric state.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Interestingly, up to 7 consecutive biphenyl base pairs can be incorporated into DNA without causing any decrease in duplex stability [32] and an NMR investigation concluded that stacking interactions were the main driving force behind the impressive stability of these UBPs. [35] The zipper-like motif thus appears to be an alluring candidate for applications such as electron transport through nucleic acids [36][37][38] or an expansion of the genetic code. [39] Besides biphenylmodified DNA, other C-nucleosides equipped with aromatic residues play central roles in numerous applications including the induction of important conformational transitions, [40] relaying electron transport through duplexes, [37,38,[41][42][43] assisting the homogenous assembly of aromatic carbon layers, [44] or labeling of oligonucleotides with fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…The B‐ to Z‐DNA transition, which plays a crucial role in biological systems, has been utilized for nanomechanical devices and nanosensors . In addition, DNA and DNA analogues have been used as templates to construct helical chromophore associations with π interactions through the precise incorporation of multiple chromophores into DNA . Such helical chromophore associations demonstrate unique properties, which differ significantly from the monomeric state.…”
Section: Introductionmentioning
confidence: 99%